Aegiochus gracilipes (Hansen, 1895) a senior synonym of Aegiochus tara Bruce, 2009 (Crustacea: Isopoda: Aegidae) - Hughes, Lauren E.; Bruce, Niel L.; Osborn, Karen (Zootaxa, 2020)
Aegiochus gracilipes Hansen, 1895 was described from a single immature specimen accompanied by three figures (Hansen 1895). Hansen (1916) subsequently reported the species without figures. Over the next 100 years A. gracilipes only appeared in the literature as a citation in larger review and cataloguing studies. Most significantly, Bruce (2009) transferred A. gracilipes from Aega Leach, 1815 to Aegiochus Bovallius, 1885, as part of a broader study redefining the morphological characters used to distinguish Aegiochus. To the present day A. gracilipes, described from the north-eastern Atlantic off the Outer Hebrides, Scotland, is known only from the original figures and its limited primary description.